2019
DOI: 10.1016/j.psyneuen.2019.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the regulation of brain IL-1β in response to chronic stress

Abstract: Elevations in brain interleukin-1 beta (IL-1β) during chronic stress exposure have been implicated in behavioral and cognitive impairments associated with depression and anxiety. Two critical regulators of brain IL-1β production during times of stress are glucocorticoids and catecholamines. These hormones work in opposition to one another to inhibit (via glucocorticoid receptors) or stimulate (via beta-adrenergic receptors: β-AR) IL-1 β production. While chronic stress often heightens both corticosterone and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…Further, this study confirmed that sex hormones were correlated with cortisol levels, thereby linking sex hormones with stressinduced cortisol responses in men and women. In support of these clinical findings, sex differences in corticosterone regulation of repeated stress-induced inflammation in rodents is also well recognized (Barnard et al, 2019). Taken together these clinical and preclinical studies provide evidence whereby, through modulating release of the anti-inflammatory hormone cortisol in the context of social stress or through direct regulation of microglia via estrogen receptors, sex hormones may be promoting exaggerated inflammatory responses in females and anti-inflammatory responses in males.…”
Section: Role Of Ovarian Hormones In Stress-related Inflammatory and mentioning
confidence: 66%
“…Further, this study confirmed that sex hormones were correlated with cortisol levels, thereby linking sex hormones with stressinduced cortisol responses in men and women. In support of these clinical findings, sex differences in corticosterone regulation of repeated stress-induced inflammation in rodents is also well recognized (Barnard et al, 2019). Taken together these clinical and preclinical studies provide evidence whereby, through modulating release of the anti-inflammatory hormone cortisol in the context of social stress or through direct regulation of microglia via estrogen receptors, sex hormones may be promoting exaggerated inflammatory responses in females and anti-inflammatory responses in males.…”
Section: Role Of Ovarian Hormones In Stress-related Inflammatory and mentioning
confidence: 66%
“…Third, the effect of chronic stress in depression could provide more information on the role of vitamin D, as it is known as a relevant risk factor of cognitive/affective depressive symptoms (35). Chronic stress induced dendritic atrophy in hippocampal pyramidal neurons (36), and affected the regulation of Interleukin 1 beta (IL-1ß) (37), only in male rats. Additionally, social isolation stress tests induced anhedonia-like behavior only in male rats, and reductions in synaptic proteins and spine density after social isolation were reversed by ketamine only in male rats (38).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are reasons to believe that after stress exposure, IL-1 β is primarily produced by microglia. This is because isoproterenol (a β -AR agonist) induces IL-1 β mRNA in cultured microglia but not in astrocytes [69], administration of minocycline prevents stress-induced increases in brain IL-1 β [40, 70], and the induction of IL-1 β after stress or metyrapone treatment (a corticosterone synthesis inhibitor) is observed in CD11b+ cells [45, 71].…”
Section: Discussionmentioning
confidence: 99%